Antibiotic resistance in the pathogenic bacteria isolated from environmental samples of the food production facilities - Yushina Yuliya; Zaiko Elena; Makhova Anzhelika; Bataeva Dagmara; Nasyrov Nasarbay (BIO Web of Conferences, 2023)
Foodborne pathogens, such as Salmonella spp. and Listeria monocytogenes, may be present at various stages of production. The overuse of antibiotics over the past few decades has led to the emergence of many antibiotic-resistant bacteria, including foodborne pathogens. We investigated the sensitivity of Salmonella spp and Listeria monocytogenes to various antibiotics. Studied strains of L. monocytogenes and Salmonella spp. they showed resistance to tetracycline, which totaled 66.7%. High resistance of strains to ampicillin was also noted (57.14%). All strains were sensitive to amikacin, azithromycin, Meropenem, ciprofloxacin, moxifloxacin, norfloxacin. All strains of Salmonella spp. were resistant to ampicillin and penicillin G. Resistance to streptomycin and trimethoprim/sulfamethoxazole was 91.7%. All strains of L. monocytogenes were resistant to nalidixic acid. 22.2% of the strains showed resistance to tetracycline and cefepime. 11.1% of the strains were resistant to chloramphenicol and trimethoprim/sulfamethoxazole.